2005
DOI: 10.1093/treephys/25.9.1139
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration patterns in boreal Scots pine glades linked to cold-induced photoinhibition

Abstract: Regeneration patterns of Pinus sylvestris L. juveniles in central Siberian glades were studied in relation to cold-induced photoinhibition. Spatial distribution of seedlings in different height classes revealed higher seedling densities beneath the canopy than beyond the canopy, and significantly higher densities of seedlings < 50 cm tall on the north side of the trees. These patterns coincided with differences in light conditions. Compared with plants on the north side of canopy trees (north-exposed), photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
3
28
1
1
Order By: Relevance
“…Whereas this study reports the first xanthophyll cycle data on higher plants in the Arctic that we are aware of, previous studies on Antarctic mosses at 66°S (Lovelock and Robinson, 2002;Robinson et al, 2005), Antarctic angiosperms in maritime Antarctica (Bascuñan-Godoy et al, 2012) and subarctic pine forests at 66°N (Louis et al, 2005;Slot et al, 2005) also reported high xanthophyll cycle pool sizes and zeaxanthin retention, although in most cases not as high as those observed in S. pulchra in this study. Although it is difficult to compare xanthophyll interconversion rates among studies, our (Z+A) dark-retention data (Figs.…”
Section: Discussioncontrasting
confidence: 60%
“…Whereas this study reports the first xanthophyll cycle data on higher plants in the Arctic that we are aware of, previous studies on Antarctic mosses at 66°S (Lovelock and Robinson, 2002;Robinson et al, 2005), Antarctic angiosperms in maritime Antarctica (Bascuñan-Godoy et al, 2012) and subarctic pine forests at 66°N (Louis et al, 2005;Slot et al, 2005) also reported high xanthophyll cycle pool sizes and zeaxanthin retention, although in most cases not as high as those observed in S. pulchra in this study. Although it is difficult to compare xanthophyll interconversion rates among studies, our (Z+A) dark-retention data (Figs.…”
Section: Discussioncontrasting
confidence: 60%
“…; Donoso et al 2007, Soto et al 2009 or in the west of England and Wales have had severe mortality or damage. Considering that partial shade from forest canopies can protect seedlings from frosts (Slot et al 2005) and changes the intensity of direct and diffuse incident light (Norman et al 1971), it might be possible to successfully plant N. dombeyi and N. alpina in high-graded forests. However, considering that the species are of low shade tolerance, the challenge is to find the proper combination of canopy protection and light availability for optimum performance of planted seedlings of Nothofagus species.…”
Section: Introductionmentioning
confidence: 99%
“…Reasonably, the old mother pines and their current offspring may be functionally important as dispersal nodes if preconditions for landscape-scale pine expansion should occur (cf. Slot et al 2005;Trant et al 2011). To some extent, this option has been sustained since the early 1990s, when scattered young pine saplings started to appear sparsely but quite regularly in the alpine tundra, 600-700 m above the permanent plots (Kullman 2007b;2007c).…”
Section: The Landscape Contextmentioning
confidence: 99%